Workplace violence against healthcare workers in the Republic of Moldova during COVID-19 pandemic: a cross-sectional study - Elena Ciobanu; Dumitru Cheptea; Svetlana Cociu; Patricia Maria Marga; Serghei Cebanu; Diana Dulf; Corinne Peek-Asa (Frontiers in Public Health)
ObjectivesThis study aimed to explore healthcare providers’ experiences with workplace violence cases before and during the COVID-19 pandemic and to identify the prevalence of risk factors.MethodsA cross-sectional study design was conducted among healthcare professionals from six hospitals in Moldova during the COVID-19 pandemic. The study included 189 medical professionals and clinical support staff.ResultsThis study surveyed 189 healthcare professionals, mostly aged 40–49 (31.7%), with physicians (43.9%) and nurses (42.3%) being predominant. Departments most represented were infectious disease (28.3%), emergency (21.4%), and intensive care (16.1%). Violence prevention training was lacking (83.6%). Hallways (38.5%) and poorly visible areas (34.3%) were leading environmental risk factors. Workplace violence affected 43.1% of participants. Physical assault and verbal threats have a strong correlation before and during the pandemic (r = 0.654; r = 0.714), but changes were not statistically significant. Female staff had lower odds of experiencing serious violence (OR = 0.43, p = 0.013). Workers with 11+ years’ experience faced fewer incidents, while those with 2–5 years faced a higher risk.ConclusionWorkplace violence remained prevalent during the COVID-19 pandemic, with statistically significant variation over time, pointing the need for ongoing prevention efforts.